Observational learning of a new motor skill: The effect of different model demonstrations - Ghorbani, S.; Bund, A. (International Journal of Sports Science & Coaching, 2016)
A central question in observational learning is which information is picked-up by the observers from a demonstration. Visual perception perspective suggested that relative motion information, such as those highlighted in point-light or stick-figure demonstrations, is extracted and used for reproducing the modeled action. This study was designed to examine this assumption by using a baseball-pitch as to-be-learnt motor task. Forty-one novice female and male adults were randomly assigned to three demonstration groups (video, stick-figure, and point-light) and a control group. Participants performed 5 trials in pretest, three blocks of 10 trial in acquisition phase, and two retention tests of 5 trials in 10 min and 7 days after last acquisition block. Intra- and inter-limb coordination patterns and movement time were measured at level of overall movement and individual movement phases as dependent variables. Results show that participants improved their coordination performance from pretest to acquisition blocks and retention tests, however, regardless of model observation. No significant difference was observed between groups in two retention tests. Analysis of movement phases showed a significant improvement in stride phase from pretest to acquisition blocks. Results are interpreted in terms of theoretical and methodological backgrounds. Further perspectives in research on observational learning are presented. ABSTRACT FROM AUTHOR